If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 50 = 16g + 2 Reorder the terms: 50 = 2 + 16g Solving 50 = 2 + 16g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-16g' to each side of the equation. 50 + -16g = 2 + 16g + -16g Combine like terms: 16g + -16g = 0 50 + -16g = 2 + 0 50 + -16g = 2 Add '-50' to each side of the equation. 50 + -50 + -16g = 2 + -50 Combine like terms: 50 + -50 = 0 0 + -16g = 2 + -50 -16g = 2 + -50 Combine like terms: 2 + -50 = -48 -16g = -48 Divide each side by '-16'. g = 3 Simplifying g = 3
| 4x+-2y=38 | | -p/7=-9 | | 2n^2+3n=0 | | 6+(12/6)/2 | | 2/3t=-10 | | -91=7p | | 2a-1=-(a+4) | | 24+9n=-3 | | 12x^2=18x-1 | | 5(m+3)+7m=3(m-9) | | 5(-7x+2)=-40 | | 3(3n+40)=54+6n | | 24=8c | | -3x-15=9x+9 | | m+4=1 | | 2x^2+3-5=0 | | 6p=-96 | | n/8=-12 | | 30=12n-18 | | -5+n=-23 | | -632=4g | | -9j-10=62 | | 8=-12+x | | 2=4h-14 | | 5w-3w= | | -6=v-4 | | 6x+8=2x-28 | | 18+5.50x=y | | J+434=-376 | | (-4x-5)=-125 | | Y=(x^2+5)2x+1 | | 2x^2+5x+15=0 |